Analysis of Factors Affecting the Use of Online Learning at English Department Students of Tadulako University - Rafika sari lasiara; Nadrun; Zarkiani Hasyim; Mochtar Marhum (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze the factors affacting students used of online learning. The research used descriptive qualitative method with open ended questionnaire to collect the data. The sample of the research was the sixth semester students of English Department at Tadulako University Palu. The sample was taken by using purposive sampling technique. The results of questionnaire are that students disagreed that online learning helped them in learning process under certain condition. From 21 total items, the researchers classified into factors, internal and external factors. The internal factor consisted of students' understanding, students' activeness, effective and efficient students. Meanwhile, the external factor consisted of media, network, and environment. Based on the data obtained, the reseacher conclude that many factors influenced students' learning process in online learning. From the two factors classification, the students' understanding in the internal factor was a big factor that, affecting their learning outcomes in the online learning process. Most students felt that they did not master the learning material as well during online learning.